2016
DOI: 10.1111/jen.12300
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of native North American Rutaceae to serve as host plants for the Asian citrus psyllid (Hemiptera: Liviidae)

Abstract: The Asian citrus psyllid, Diaphorina citri Kuwayama, a vector of citrus huanglongbing, is now present in all citrus-producing states in the USA and Mexico. In addition to citrus, the insect can reproduce on several other plant species in the Rutaceae family; orange jasmine (Murraya spp.) and curry leaf (Bergera koenigii) are among its preferred hosts. There are several indigenous Rutaceae species in North America, and some are popular ornamentals. A study was therefore initiated to determine the suitability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
(49 reference statements)
1
21
0
4
Order By: Relevance
“…The growth index, that is, the effect of nutritional quality of host plants on the survival rate and development times of insects (Sétamou et al, 2015(Sétamou et al, , 1999, was highest in M. koenigii followed by Diaphorina citri, a close relative of ACT reproduction, differed significantly when reared on different host plants (Pimpinato et al, 2017). In general, plant quality influences the growth, development and reproductive potential of insects (Slansky & Scriber, 1985).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The growth index, that is, the effect of nutritional quality of host plants on the survival rate and development times of insects (Sétamou et al, 2015(Sétamou et al, , 1999, was highest in M. koenigii followed by Diaphorina citri, a close relative of ACT reproduction, differed significantly when reared on different host plants (Pimpinato et al, 2017). In general, plant quality influences the growth, development and reproductive potential of insects (Slansky & Scriber, 1985).…”
Section: Discussionmentioning
confidence: 98%
“…The growth index, that is, the effect of nutritional quality of host plants on the survival rate and development times of insects (Sétamou et al, ), was highest in M. koenigii followed by C. anisata and T. nobilis . Similarly, number of emerged nymphs and the number of emerging adults were highest in M. koenigii followed by C. anisata and then T. nobilis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although volatiles have been implicated in the attraction of psyllids for feeding and reproduction, other factors such as the nutritional status of the host plant cannot be overlooked. For instance, Sétamou, Graça, and Sandoval () observed that D. citri , when raised on different host plants, showed considerable variation in terms of feeding and reproductive preferences.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found higher mean numbers of ACT immature stages (eggs and nymphs), galls and infested leaves on citrumelo than on the other cultivars, which might be partially attributed to volatiles produced by citrumelo. This For instance, Sétamou, Graça, and Sandoval (2016) observed that D. citri, when raised on different host plants, showed considerable variation in terms of feeding and reproductive preferences.…”
Section: African Citrus Triozid Distribution Abundance and Damage mentioning
confidence: 99%